2016
DOI: 10.7554/elife.18009
|View full text |Cite
|
Sign up to set email alerts
|

Visual attention is available at a task-relevant location rapidly after a saccade

Abstract: Maintaining attention at a task-relevant spatial location while making eye-movements necessitates a rapid, saccade-synchronized shift of attentional modulation from the neuronal population representing the task-relevant location before the saccade to the one representing it after the saccade. Currently, the precise time at which spatial attention becomes fully allocated to the task-relevant location after the saccade remains unclear. Using a fine-grained temporal analysis of human peri-saccadic detection perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 39 publications
9
35
0
Order By: Relevance
“…In our model, attention is available at the attention position immediately after the saccade as the remapped attention pointer is then shifted to this position. Taking into account that the decision process in the experiment itself needs time (processing the visual input and making the decision), this fits to the data of Yao et al (2016). In addition to attentional cuing, we showed that attention may also be induced by an endogenous attention signal.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…In our model, attention is available at the attention position immediately after the saccade as the remapped attention pointer is then shifted to this position. Taking into account that the decision process in the experiment itself needs time (processing the visual input and making the decision), this fits to the data of Yao et al (2016). In addition to attentional cuing, we showed that attention may also be induced by an endogenous attention signal.…”
Section: Discussionsupporting
confidence: 83%
“…For instance, Marino and Mazer (2018) find in V4 only evidence for predictive remapping of attention but not for lingering of attention whereas Yao, Treue, and Krishna (2018) detect in MT only lingering but no remapping of attention. Yao et al (2016) even find neither remapping nor lingering of attention in a psychophysical study with humans though these results are may be biased by their experimental design where remapped and lingering attention position were not only irrelevant, but importantly these positions were never target locations that tested the amount of attention. Lisi, Cavanagh, and Zorzi (2015) suggest, that spatial updating of attention depends on the setup of the experiment, namely whether visual objects, which can serve as spatial landmarks, are presented or not.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…At the behavioral level, this compensation could result in anticipatory deployment of spatial attention to the retinal location a visual stimulus will occupy after the saccade [6][7][8][9] . Such anticipatory deployment could explain observations that attention is allocated at a spatial target location almost immediately after a saccade 7,10 .…”
Section: Introductionmentioning
confidence: 96%